(3YOI GdHhfis - (3CMeO Hf Ydj Hf jhSa, CHh GdYHGS GdHhfj,J (B622 (3g` s
(3ChdgG (B:s
(3bGd CHhYHOGddg Gdbhd Ydi SQ NGJe s
(3BNQgG (B:s
(3ai Qb ZRGd hjfLR jchf dbVA GdMhGjL s
(3Vef eLehY , JQJjHgG (B: (3GdKGef YTQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B174 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B25s
(3eUOQ GbJfGA GdCUd (B:s
(3GeHQhRjGfG (B(B 58) s
Keywords: (3GdMQha h GdChaGbs